Transplantation of Human Dental Pulp-Derived Stem Cells Protects against Heatstroke in Mice. Issue 5 (May 2015) - Tseng, Ling-Shu; Chen, Sheng-Hsien; Lin, Mao-Tsun; Lin, Ying-Chu
Stem cells from human exfoliated deciduous tooth pulp (SHED) is a promising approach for the treatment of stroke and spinal cord injury. In this study, we investigated the therapeutic effects of SHED for the treatment of multiple organ (including brain, particularly hypothalamus) injury in heatstroke mice. ICR male mice were exposed to whole body heating (WBH; 41.2°C, relative humidity 50-55%, for 1 h) and then returned to normal room temperature (26°C). We observed that intravenous administration of SHED immediately post-WBH exhibited the following therapeutic benefits for recovery after heatstroke: (a) inhibition of WBH-induced neurologic and thermoregulatory deficits; (b) reduction of WBH-induced ischemia, hypoxia, and oxidative damage to the brain (particularly the hypothalamus); (c) attenuation of WBH-induced increased plasma levels of systemic inflammatory response molecules, such as tumor necrosis factor-a and intercellular adhesion molecule-1; (d) improvement of WBH-induced hypothalamo-pituitary-adrenocortical (HPA) axis activity (as reflected by enhanced plasma levels of both adrenocorticotrophic hormone and corticosterone); and (e) attenuation of WBH-induced multiple organ apoptosis as well as lethality. In conclusion, post-WBH treatment with SHED reduced induction of proinflammatory cytokines and oxidative radicals, enhanced plasma induction of both adrenocorticotrophic hormone and corticosterone, and improved lethality in mouse heatstroke. The protective effect of SHED may be related to a decreased inflammatory response, decreased oxidative stress, and an increased HPA axis activity following the WBH injury.